Work Dicipline Can Moderates The Influence of Self-Reward on Job Satisfaction - Sinaulan, Jeffry H.; Farawowan, Fauziah F.; Sumarno, Sumarno; Sakalessy, Aleksander; Budiman, Ronny Regawa (PT. Sharia Journal and Education Center, 2026)
This study aims to investigate the role of work discipline as a moderating variable in the relationship between self-reward and employee job satisfaction. In the modern work era, the phenomenon of self-reward has emerged as an individual coping mechanism against workload, but its effectiveness in generating long-term job satisfaction is often questioned without self-regulation. Using a quantitative approach with the Moderated Regression Analysis (MRA) method, this study examines how an individual's level of discipline strengthens or weakens the impact of self-appreciation on their professional satisfaction. The results show that self-reward has a positive effect on job satisfaction, but work discipline plays a crucial role as a moderator that ensures that self-reward behavior does not slip into procrastination. High work discipline is found to optimize this relationship, creating a balance between psychological well-being and organizational productivity.